European recommendations for management of immune checkpoint inhibitors‐derived dermatologic adverse events. The EADV task force 'Dermatology for cancer patients' position statement. (15th December 2021) - Apalla, Z.; Nikolaou, V.; Fattore, D.; Fabbrocini, G.; Freites‐Martinez, A.; Sollena, P.; Lacouture, M.; Kraehenbuehl, L.; Stratigos, A.; Peris, K.; Lazaridou, E.; Richert, B.; et al.
Abstract: The introduction of immune checkpoint inhibitors (ICIs) opened a new era in oncologic therapy. The favourable profile of ICIs in terms of efficacy and safety can be overshadowed by the development of immune‐related adverse events (irAEs). Dermatologic irAEs (dirAEs) appear in about 40% of patients undergoing immunotherapy and mainly include maculopapular, psoriasiform, lichenoid and eczematous rashes, auto‐immune bullous disorders, pigmentary disorders, pruritus, oral mucosal lesions, hair and nail changes, as well as a few rare and potentially life‐threatening toxicities. The EADV task force Dermatology for Cancer Patients merged the clinical experience of the so‐far published data, incorporated the quantitative and qualitative characteristics of each specific dirAEs, and released dermatology‐derived, phenotype‐specific treatment recommendations for cutaneous toxicities (including levels of evidence and grades of recommendation). The basic principle of management is that the interventions should be tailored to serve the equilibrium between patients' relief from the symptoms and signs of skin toxicity and the preservation of an unimpeded oncologic treatment.